Bifurcation Asymmetry of Small Coronary Arteries in Juvenile and Adult Mice - Feng, Yundi; Wang, Xuan; Fan, Tingting; Li, Li; Sun, Xiaotong; Zhang, Wenxi; Cao, Minglu; Liu, Jian; Li, Jianping; Huo, Yunlong (Frontiers in Physiology, 2018)
Background: Microvascular bifurcation asymmetry is of significance for regulation of coronary flow heterogeneity during juvenile and adult growth. The aim of the study is to investigate the morphometric and hemodynamic variation of coronary arterial bifurcations in mice of different ages. Methods: Pulsatile blood flows were computed from a Womersley-type model in the reconstructed left coronary arterial (LCA) trees from Micro-CT images in normal mice at ages of 3 weeks, 6 weeks, 12 weeks, 5-6 months, and >8 months. Diameter and flow ratios and bifurcation angles were determined in each bifurcation of the LCA trees. Results: The blood volume and inlet flow rate of LCA trees increase and decrease during juvenile and adult growth, respectively. As vessel diameters decrease, the increased ratios of small to large daughter vessel diameters (D_s/D_m) result in more uniform flows and lower velocities. There are significant structure-functional changes of LCA trees in mice of >8 months compared with mice of <8 months. As D_s/D_m increases, the variation trend of bifurcation angle during juvenile growth is different from that during adult growth. Conclusions: Although inlet flows are different in adult vs juvenile mice, the adult still have uniform flow and low velocity. This is accomplished through a decrease in diameter. The design ensures ordered dispersion of red cells through asymmetric branching patterns into the capillaries.